2008
DOI: 10.1002/lsm.20592
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of selective retina treatment (SRT) by means of 8 ns laser pulses in a rabbit model

Abstract: Background: It has been shown that selective retina treatment (SRT) using a train of 1.7 microseconds laser pulses allows selective damage of the retinal pigment epithelium (RPE) while sparing the adjacent photoreceptors and thus avoiding laser scotoma. It was the purpose of this work to investigate SRT laser effects with Q-switched pulses of only 8 nanoseconds in duration by evaluating the angiographic and ophthalmoscopic damage thresholds and the damage range by histology in a rabbit model. Materials and Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…The latter study demonstrated no collateral damage either, meaning that in both the latter and the current studies, RPE cells could be specifically targeted. The present data, in addition, are in approximate agreement with the studies of Roider and colleagues, who have used 8‐nanosecond in comparison with microsecond pulse lasers to selectively ablate RPE cells 34, 45, 46. These authors concluded, however, that their nanosecond pulses resulted in a reduced safety range compared with the microsecond lasers in terms of collateral photoreceptor damage; the more favorable outcomes described in the present study may result from the use of shorter 3 nanoseconds pulses, thereby applying reduced energy to the system.…”
Section: Discussionsupporting
confidence: 92%
“…The latter study demonstrated no collateral damage either, meaning that in both the latter and the current studies, RPE cells could be specifically targeted. The present data, in addition, are in approximate agreement with the studies of Roider and colleagues, who have used 8‐nanosecond in comparison with microsecond pulse lasers to selectively ablate RPE cells 34, 45, 46. These authors concluded, however, that their nanosecond pulses resulted in a reduced safety range compared with the microsecond lasers in terms of collateral photoreceptor damage; the more favorable outcomes described in the present study may result from the use of shorter 3 nanoseconds pulses, thereby applying reduced energy to the system.…”
Section: Discussionsupporting
confidence: 92%
“…Framme et al irradiated chinchilla rabbits using a Nd:YAG 532‐nm laser with 8‐ns pulse lengths. The authors reported that RPE damage with sparing of the photoreceptor layer was not consistently achievable in this model …”
Section: Short‐pulse Duration Lasersmentioning
confidence: 86%
“…Also the choroid was intact, which indicates that the oxygen‐rich choroid can help regeneration of fully functional RPE cells. Within days after laser treatment, the debris of damaged RPE cells was phagocytized by bystander RPE cells sliding in from the neighbourhood or by macrophages originating from the choriocapillaris . In contrast with selective lesions, the full‐thickness structure of the retina was disrupted and disorganized in the conventional laser lesions.…”
Section: Discussionmentioning
confidence: 99%